Pengungkapan Enterprise Risk Management Terhadap Nilai Perusahaan: Keywords: Enterprise Risk Management; Firm Value; Firm Size; Industry Type - Siti Nor Faizah; Pujiono . (Jurnal Akuntansi, 2022)
This study aims to determine the effect of Enterprise Risk Management disclosure on firm value with firm size and industry type as control variables. Sample of this study is all company of various sectors which listed on the Indonesia Stock Exchanged (IDX) during 2017. The method used in this study is quantitative by collecting documentation through annual reports. Enterprise Risk Management was analyzed using content analysis method and firm value was proxied using Tobin’s Q. Sample selection using Slovin method. Data were analyzed using multiple linear regression and then data processed using SPSS 22. The result of this study show that Enterprise Risk Management disclosure has no influence on firm value.